Binti Shujaaz - Komba, Lucky; Mpenze, Neema; Mbugua, Narayan; Biamah, Stephan; Deacon, Bridget; Galiè, Alessandra; Achandi, Esther; Omondi, Immaculate A.; Campbell, Zoë A.; Jeremiah, Adolf; Jumba, Humphrey; Ngoteya, Godfrey; et al. (2024)
Binti Shujaaz means “heroine” in Swahili, a fitting name for the young women who are persevering in chicken keeping despite restrictive gender norms in their communities that can limit young women in agri-business. This comic book written in Swahili was distributed in Tanzania in 2024 to support community conversations about norms. The stories were informed by research on social norms conducted by the International Livestock Research Institute.